The Effect of Counseling on Family Planning Acceptors in Making Decisions on Contraceptives During the Postpartum Period at the Jatiluhur Health Center, Purwakarta Regency, Indonesia - Dian Setiawati, Yeni Tegar (HM Publisher, 2024)
Indonesia is a country with a fairly large population, so efforts are needed to control population growth through the family planning (KB) program. One of the factors that influence the success of a family planning program is the decision-making of appropriate contraceptives by prospective family planning acceptors. Counseling is an effort to improve appropriate contraceptive decision-making. The aim of this research is to determine the effect of counseling on family planning acceptors in making decisions about contraceptives during the postpartum period at the Jatiluhur Health Center, Purwakarta Regency, Indonesia. This research uses a quasi-experimental research design with a pretest-posttest control group design. The research population was all postpartum women who gave birth at the Jatiluhur Health Center, Purwakarta Regency, in January-March 2023. The research sample was 60 people, consisting of 30 people in the experimental group and 30 people in the control group. Data was collected using a family planning counseling questionnaire. Data analysis used the t-test. The results of the research show that there is an influence of counseling on family planning acceptors in making decisions about contraceptives during the postpartum period at the Jatiluhur Health Center, Purwakarta Regency, Indonesia. The experimental group that was given counseling had a higher contraceptive decision-making score than the control group that was not given counseling. The conclusion of this study is that counseling is effective in improving contraceptive decision-making among family planning acceptors during the postpartum period.